Project summary: 'Structured PhD in Research Integrity and Impact in an Open Scholarship Era' Module' [(RIOSE] - Brennan, Niamh (Trinity College Dublin, The University of Dublin, 2020)
Based upon feedback from Trinity schools and students, ‘Research Integrity and Impact in an Open Scholarship Era’ – an existing module for incoming doctoral students – will be redesigned from a pedagogical perspective and rebuilt from the ground up, making it applicable across multiple disciplines and contexts. In partnership with students and faculty stakeholders, the new mandatory wholly-online 5 ECTS module will be contextually embedded while maximising the value of shared disciplinary good practice. This is a summary of this project which is funded by the National Forum for the Enhancement of Teaching and Learning SATLE.
Keywords: Instructional design; Open Science training